Equity, Bonds, and Bank Debt: Capital Structure and Financial Market Equilibrium under Asymmetric Information - Bolton, Patrick; Freixas, Xavier (Journal of Political Economy, 2000)
This paper proposes a model of financial markets and corporate finance, with asymmetric information and no taxes, where equity issues, bank debt, and bond financing coexist in equilibrium. The relationship banking aspect of financial intermediation is emphasized: firms turn to banks as a source of investment mainly because banks are good at helping them through times of financial distress. This financial flexibility is costly since banks face costs of capital themselves (which they attempt to minimize through securitization). To avoid this intermediation cost, firms may turn to bond or equity financing, but bonds imply an inefficient liquidation cost and equity an informational dilution cost. We show that in equilib‐rium the riskier firms prefer bank loans, the safer ones tap the bond markets, and the ones in between prefer to issue both equity and bonds. This segmentation is broadly consistent with stylized facts.